Determination of Radiation Dose from Routine X-ray Examination at Three Selected Hospitals in AlNajaf, Iraq - Bakir, Hussien Abid Ali; Al-hchaimi, Talib Abdulridha; Amran, Aymen S.; Al Zurfi, Aqeel H. (Iraqi Journal of Science, 2019)
People who undertaken different X-ray examinations are already exposed to ionizing radiation which causes biological effects. Therefore assessing the patient radiation dose is a prerequisite element in optimizing the X-ray practice and to avoid the unnecessary radiation dose. The aim of this research is to assess the skin radiation dose for those patients who undertaking routine X-ray examinations in selected three hospitals in Al Najaf city. Three X-ray units were involved in this experimental study; these were belonging to three hospitals in Al Najaf city-Iraq, namely Al-Sadder teaching hospital, Al-Hakeem general hospital and Al-Zahraa hospital. Data of exposure parameters (tube potential (kVp), tube current (mAs) and source to detector distance (d cm)). The data were collected from 160 patients exposed to radiation during different X-ray examinations. Patients were chosen to be within adult range (>18 years) and the selection was random (male and female). Patient skin dose was calculated mathematically using an established formula depending on the recorded exposure factor (kVp, mAs and d). Different X-ray examinations were considered, namely skull Posterior –anterior (PA), skull Lateral (LAT), chest PA, chest LAT, abdomen Anterior-posterior (AP), pelvis AP, lumbar spine AP and lumbar LAT. The average skin dose for all X-ray examinations considered in this research were as follow: 0.9, 0.76, 0.23, 0.41, 1.85, 1.82, 2.03 and 3.44 mGy, for skull PA, skull LAT, chest PA, chest LAT, abdomen AP, pelvis AP, lumbar spine(LS) AP and Lumbar spine (LS)LAT respectively. The results demonstrate that the dose values were comparable to those that were previously reported in published reference.